Attract and kill, an effective technique to manage apple maggot, Rhagoletis pomonella [Diptera : Tephritidae] in high density Quebec apple orchards - Bostanian, N.J.; Racette, G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
"Attract and kill" is an effective technique to control apple maggot (Rhagoletis pomonella) in apple orchards. It provided 98.5 to 100% clean fruit at harvest in McIntosh, Liberty, Royal Gala and Jonagold cvs. The traps consisted of yellow boards (28 cm x 21.5 cm) sandwiched between the two halves of red spheres (9 cm diam). They were sprayed with 12.5 and 6.3% cypermethrin or 1.3 and 1.7% deltamethrin in de-odorized kerosene, loaded with butyl hexanoate in semi-permeable sachets. The traps were hung on branches 1.20-1.70 m above the ground. They were placed on the periphery of the plot and positioned so as to be visible from outside the tree canopy. The number of traps per plot was a function of the length of the plot opposite a possible entry site of apple maggot. In columns opposite a forest, entry site of apple maggot into the plot, the traps in a column were at 2-3 m intervals (0.3-0.5 traps m-1). A trap was also placed on every tree of the first and last row of a column. The columns were 4-5.5 m apart (0.18-0.25 traps m-1). Opposite to prairie grass or a chemically treated plot the traps were at 2-6 m intervals (0.17-0.5 traps m-1) in a column. On the row, the distance between adjacent traps was 4 to 12 m (0.08-0.25 traps m-1). To achieve commercially acceptable apple maggot control in cvs. McIntosh, Liberty, Gala and Jonagold apples with "attract and kill" technique, the activity of the pest should not exceed 13 flies per four traps placed on the periphery of the plot, in other words, 1.6 times the action threshold for the apple maggot in Quebec apple orchards.